100 YEARS OF VITAMIN D: Effect of serum vitamin D level before ovarian stimulation on the cumulative live birth rate of women undergoing in vitro fertilization: a retrospective analysis. Issue 2 (14th February 2022) - Ko, Jennifer K Y; Shi, Jinghua; Li, Raymond H W; Yeung, William S B; Ng, Ernest H Y
Abstract : Objective: Vitamin D receptors are present in the female reproductive tract. Studies on the association between serum vitamin D level and pregnancy rate of in vitro fertilization (IVF) showed inconsistent results and focused on a single fresh or frozen embryo transfer cycle. The objective of our study was to evaluate if serum vitamin D level before ovarian stimulation was associated with the cumulative live birth rate (CLBR) of the first IVF cycle. Design: Retrospective cohort study. Methods: Women who underwent the first IVF cycle from 2012 to 2016 at a university-affiliated reproductive medicine center were included. Archived serum samples taken before ovarian stimulation were analyzed for 25(OH)D levels using liquid chromatography-mass spectrometry. Results: In total, 1113 had pregnancy outcome from the completed IVF cycle. The median age (25th–75th percentile) of the women was 36 (34–38) years and serum 25(OH)D level was 53.4 (41.9–66.6) nmol/L. The prevalence of vitamin D deficiency (less than 50 nmol/L) was 42.2%. The CLBR in the vitamin D-deficient group was significantly lower compared to the non-deficient group (43.9%, 208/474 vs 50.9%, 325/639, P   = 0.021, unadjusted), and after controlling for women's age, BMI, antral follicle count, type and duration of infertility. There were no differences in the clinical/ongoing pregnancy rate, live birth rate and miscarriage rate in the fresh cycle between the vitamin D deficient and non-deficient groups. Conclusions: Vitamin D deficiency was prevalent in infertile women in subtropical Hong Kong. The CLBR of the first IVF cycle in the vitamin D-deficient group was significantly lower compared to the non-deficient group.